The Effect of Mulberry Fruits Consumption on Lipid Profiles in Hypercholesterolemic Subjects: A Randomized Controlled Trial - Anchalee Sirikanchanarod,; Akkarach Bumrungpert,; Wiroje Kaewruang,; Tipanee Senawong ,; Patcharanee Pavadhgul, (Journal of Pharmacy and Nutrition Sciences, 2016)
Mulberry (Morus alba) fruit is abundant nutrients and phytochemicals, especially anthocyanins. Mulberries have anti-oxidant and anti-hyperlipidaemic effects both in vitroand animal models. However, the effect of mulberry fruits on lipid profiles in human is unknown. The aim of this study was to determine the effect of mulberry fruit consumption on lipid profiles in hypercholesterolemic subjects. This study is an experimental study, with a randomized controlled trial. Fifty-eight hypercholesterolemic subjects (aged 30-60 years) were recruited. The intervention group received freeze-dried mulberry 45 g (325 mg anthocyanins) per day for six weeks. The control group had their usual dietary intake for the same period of time. After six weeks, mulberry consumption significantly decreased the level of total cholesterol (TC) (- 3.73 % vs. 3.33 %, p < 0.001) and low density lipoprotein cholesterol (LDL-C) (- 6.53 % vs. 0.15 %, p < 0.001) compared to the control group. No change in triacylglycerol (TAG) and high density lipoprotein cholesterol (HDL-C). Mulberry consumption ameliorates TC and LDL-C concentrations. The mulberry fruits may be an alternative therapy for hypercholesterolemia patients and a cardiovascular disease protective for people in general.